2021
DOI: 10.1590/2317-1545v43230606
|View full text |Cite
|
Sign up to set email alerts
|

Germination of tucumã (Astrocaryum aculeatum G. Mey.) as a function of thermal pretreatment and stratification temperature

Abstract: Germination of tucumã (Astrocaryum aculeatum G. Mey.) seeds is slow and although the removal of the endocarp favors the speed of the process, the time is still considered long. Thus, this study aimed to investigate the effects of different pretreatment and stratification temperatures on the germination of tucumã seeds. Two experiments were set up. The first experiment was conducted using a completely randomized design in a factorial scheme and seedling emergence was evaluated as a function of the pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In Astrocaryum acaule Mart., germinative bud formation occurs, on average, at 113 days, with minimum and maximum time of 14 and 250 days, respectively (Corrêa et al, 2019). The removal of the endocarp, followed by imbibition and stratifi cation at alternating temperature (26-40 ºC), favors the germination of A. aculeatum seeds (Ferreira et al, 2021). Baskin and Baskin (2014) observed that the seeds of most palm trees have morphophysiological type dormancy or are morphologically dormant, something that needs to be proven for Amazonian species.…”
Section: Introductionmentioning
confidence: 99%
“…In Astrocaryum acaule Mart., germinative bud formation occurs, on average, at 113 days, with minimum and maximum time of 14 and 250 days, respectively (Corrêa et al, 2019). The removal of the endocarp, followed by imbibition and stratifi cation at alternating temperature (26-40 ºC), favors the germination of A. aculeatum seeds (Ferreira et al, 2021). Baskin and Baskin (2014) observed that the seeds of most palm trees have morphophysiological type dormancy or are morphologically dormant, something that needs to be proven for Amazonian species.…”
Section: Introductionmentioning
confidence: 99%